Efficacy of Peritoneal Drainage for Focal Intestinal Perforation - Shunusuke Watanabe; Tatsuya Suzuki; Yasuhiro Kondo; Atsuki Naoe; Naoko Uga; Toshihiro Yasui; Fujio Hara; Masafumi Miyata; Hiroko Boda; Tetsushi Yoshikawa (EL-Med-Pub, 2018)
Objective: Focal intestinal perforation (FIP), which is characterized by the lack of inflammatory infiltration peripheral to the perforation, develops with few premonitory symptoms. The treatment typically involves laparotomy for drainage or percutaneous drain insertion. We retrospectively investigated the efficacy and risks associated with laparotomy-assisted drainage and peritoneal drainage (PD) for FIP. Study Design: This was a retrospective, comparative study. Results: We retrospectively evaluated seven infants with FIP who were admitted to the neonatal intensive care unit between April 2007 and March 2017. Five infants were administered indomethacin and six were administered steroids. The PD group had significantly higher birth weight, higher C-reactive protein (CRP) levels, and shorter operating times. In addition, they gained weight postoperatively but often required adjuvant therapy for bowel function. There was no significant difference between the groups regarding the time to post-operative full feeding, and all infants showed improved physical appearance. Conclusions: PD under local anesthesia can be considered for treating infants with FIP who have elevated CRP levels and poor general condition. We think management of this condition is still challenging in our experience, and it is necessary to continue in the future.